Revealing observatory networks through object stories: Observatory audiences - Rebekah Higgitt; Susana Biro; Pedro M P Raposo (Science Museum Group Journal, 2023)
Like the contributions to the other papers in this collection (‘Object itineraries’ and ‘Instrumental networks’), those in this final section explore instrumental networks and object itineraries in order to tell new histories of observatory sites and their associated networks. (For a discussion of the genesis and thinking behind the collection of papers see the ‘Introduction’). Here, however, they focus on object stories that highlight the opportunities for and importance of communicating with those outside the scientific community. They show, however, a wide range of potential and actual audiences to be mediated between, from closely associated scientific institutions and those holding the purse strings within government, to groups making up the local civic society and a wider and more diffuse audience for scientific outputs and achievements. The objects explored here are an 1850s model of electrically triggered time signals, associated with those at the Royal Observatory, Edinburgh; a late nineteenth-century astrographic telescope that, with approval of scientific and governmental audiences, brought the National Astronomical Observatory of Mexico into an international project and subsequently found new audiences through public display and artistic intervention; and a photoelectric relay that advertised the Yerkes Observatory to the Chicago and visiting public by forming part of a stunt, whereby the light of a distant star triggered the lighting of the 1933 Century of Progress Exposition.